Wireless Nurse Call System Using IoT Implementation - ASTUTIK Rini Puji; WINARNO Hendra Ari; ELIYANI; WAHYUNI Risma (Journal of Electrical and Electronics Engineering, 2021)
A spreading of updating technology recently encourages many scientists to explore implementing it as a daily activity. The important part of implementation technology is in the health field. One of them is the Nurse Call system which is very important in every hospital. Many hospitals use a wired Nurse Call system which needs many cables to connect to the monitor room. With a lot of cables, there will be much effort needed for finding the broken or loose cables, if any, so that the connection can be maintained. This research proposed to solve this issue by using IoT implementation on wireless nurse call system. The proposed prototype contains raspberry pie as the collecting data from each node and placed it at the monitor room, router as communication between raspberry pie and each node and the node itself by using node MCU that is placed at the patient room. The simulation shows that the system of this proposed prototype can be managed to communicate successfully between each node and monitor the room. To exam the performance, it uses three scenarios for testing, and those scenarios can be executed appropriately to the system.